PENGARUH PENERAPAN MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA E-MODUL UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR KIMIA SISWA PADA MATERI KECEPATAN REAKSI - Tio Fanny Elisabeth Hutasoit; Haqqi Annazili Nasution (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effect of implementing the PBL model assisted by e-module media on learning motivation and the improvement of students' learning outcomes on the reaction rate material, as well as to determine the correlation between learning motivation and the improvement of learning outcomes. The sample in this study was selected randomly, with Class XI-MIA-3 as the experimental class and Class XI-MIA-5 as the control class. Hypothesis testing was conducted using an independent sample t-test with a significance level of α = 0.05. The hypothesis is accepted if the Sig. (2-tailed) value < 0.05. The results of t-test on learning motivation yielded a t-count value of 9.317 with a significance of 0.000 < 0.05, which means Ha is accepted and H0 is rejected. Testing on the pre-test data resulted in a t-value of -1.944 with a significance of 0.057 > 0.05. In contrast, the post-test results showed a t-value of 12.656 and a significance of 0.000 < 0.05. The experimental class outperformed the control class by an average difference of 24.833 points, with a 95% confidence interval ranging from 20.906 to 28.761. Thus, Ha is accepted and H0 is rejected. Furthermore, for correlation, referring to Guilford's criteria, in the experimental class, a very strong positive correlation was found between learning motivation and learning outcomes with a correlation coefficient of r = 0.847 and a significance of 0.000 < 0.01. Such a high correlation indicates that about 71.7% (r² = 0.717) of the variation in student learning outcomes can be explained by their level of motivation.